EFFICACY OF INFECTIOUS BRONCHITIS DISEASE VACCINES AS MEASURED BY VIRAL SHED AFTER VIRULENT CHALLENGE IN BROILER - Sahar Hamdi Abdulmaged (Basrah Journal of Veterinary Research)
Infectious bronchitis threatens the poultry industry throughout the world, The control of IB of the big problems in the world because of the wide variations in serotypes and development in the virulence of strains from time to time, and nature is very contagious, the rapid evolution in the specific tissue tropism and recombinants because of the synchronization of infection with different virus types and the use of live vaccines.found that the IB virus which is isolated from the recent outbreak is the same serotype but the difference genotype compared with the strains of current vaccine. Previous studies have indicated that the broiler vaccination with inactivated vaccines showed significantly less virus shed if challenge with the homologous vaccines (same genotype viruses) as compared with birds that vaccination genetically heterologous vaccines. The current study compared the extent of protection resulting from vaccination with live Commercial vaccines(Volvac® IB Mass MLV, Poulvac® IB Primer (D274), Avipro® IB M48 and mixed vaccine from (Volvac®, Poulvac® and Avipro®)). Vaccinates werechallenged with virulent field isolate (Variant2) strain. Weekly post-vaccination, collected serum for analytical knowledge of the amount of antibodies using hemagglutiation inhibition test against all vaccine antigens used in the experiment after challenge with field virulent (Variant2 isolate), examine the birds daily to monitor the morbidity and mortality rates in selected periods for shedding virus by real time PCRto detect and quantitate the IBV viral copy number from clinical samples.After challenge with (Variant2) birdsvaccinated with mixed vaccine revealed less shedding virus compared to (Volvac®, Poulvac® and Avipro®)- vaccinated birdsboth separately.Genotypic differences between the vaccines and the challenge virus do not reduce the ability of vaccines to protect against the disease, but genotypic similarities reduce the virus shed and limiting its spread. The use of same249